Impact of a Nurse-Led Intervention on Symptom Severity and Life Satisfaction in Patients with Irritable Bowel Syndrome - A Quasi-Experimental Study - Chithra Gopalan,; K. Premkumar,; Shankar Shanmugam Ragendran,; Duraikannu Anandhi,; Jency Indira kuppan,; Kavitha Ethiraj, (The Bioscan, 2025)
Irritable Bowel Syndrome (IBS) is a prevalent functional gastrointestinal condition characterized by abdominal pain, bloating, and erratic bowel movements, which considerably diminishes patients' quality of life and psychological health. This study aimed to assess the efficacy of a structured nurse-led intervention on symptom severity and life satisfaction in patients with IBS. A quasi-experimental one-group pre- and post-test design was executed over four weeks at the Institute of Medical Gastroenterology, Rajiv Gandhi Government General Hospital, Chennai. Sixty patients aged 18 to 60 years, diagnosed with irritable bowel syndrome (IBS), were selected by a non-probability consecutive sampling procedure. Data were collected using a socio-demographic questionnaire, clinical checklist, the IBS Symptom Severity Scale (IBS-SSS), and the Work and Social Life Satisfaction Scale (WSLS). The intervention comprised a 40–45 minute session focusing on IBS patho-physiology, dietary guidance (low FODMAP diet), lifestyle changes, stress reduction, and coping techniques. Post-intervention results showed that the proportion of patients with mild symptoms increased from 26.67% to 80%, while those with moderate symptoms decreased from 73.33% to 20%. The mean IBS-SSS score significantly decreased from 199.46 ± 51.97 to 104.58 ± 38.92 (p < 0.001). Life satisfaction significantly improved, with WSLS scores increasing from 14.77 ± 5.59 to 23.85 ± 4.77 (p < 0.001). Symptom severity was significantly associated with age and gender, while life satisfaction was linked to family income, family structure, and co-morbidities. These findings suggest that nurse-led interventions are effective in improving both physical and psychological outcomes in IBS patients and should be integrated into standard care protocols.